Syzygium snowianum (Myrtaceae) a new canopy species from the Southern Escarpment of Papua New Guinea - Takeuchi, Wayne N (Phytotaxa, 2015)
Syzygium snowianum is described from previously inaccessible environments in southern Papua New Guinea. The new species is closest to S. ubogoense but is easily distinguished by its taller stature and yellow flowers.